2009
DOI: 10.1371/journal.pone.0007499
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Monolaurate and Dodecylglycerol Effects on Staphylococcus aureus and Toxic Shock Syndrome Toxin-1 In Vitro and In Vivo

Abstract: BackgroundGlycerol monolaurate (GML), a 12 carbon fatty acid monoester, inhibits Staphylococcus aureus growth and exotoxin production, but is degraded by S. aureus lipase. Therefore, dodecylglycerol (DDG), a 12 carbon fatty acid monoether, was compared in vitro and in vivo to GML for its effects on S. aureus growth, exotoxin production, and stability.Methodology/Principal FindingsAntimicrobial effects of GML and DDG (0 to 500 µg/ml) on 54 clinical isolates of S. aureus, including pulsed-field gel electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Therefore, other lipids reported to kill S. aureus were tested to determine if these molecules functioned by triggering the leakage of cellular components. 1-Laurylglycerol (12-MG) has antibacterial activity against S. aureus (35,45) and is regarded as a safe food preservative. Because lauric acid (12:0) was a moderately toxic fatty acid (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, other lipids reported to kill S. aureus were tested to determine if these molecules functioned by triggering the leakage of cellular components. 1-Laurylglycerol (12-MG) has antibacterial activity against S. aureus (35,45) and is regarded as a safe food preservative. Because lauric acid (12:0) was a moderately toxic fatty acid (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…optiBalance tampons in Europe. Other molecules that could be applied to mucosal surfaces and devices to reduce the risk of staphylococcal and streptococcal illnesses have also been identified (306)(307)(308)(309), including agents that prevent superantigen production and those that stabilize mucosal surfaces.…”
Section: Preventing Superantigen Production By Mucosal Microbicides Amentioning
confidence: 99%
“…The production of exotoxins by S. aureus was inhibited at monolaurin concentration that did not inhibit bacterial growth. 14,17,34,35 Monolaurin has 12 carbon molecules in its fatty acid backbone chain, which makes it span exactly one-half the width of a lipid bilayer. 36 Interestingly, it has been reported that the optimum chain length of fatty acids and their corresponding monoglycerides to achieve the maximum antibacterial activity is 12 carbons.…”
Section: Antibacterial Properties Of Ml-lncsmentioning
confidence: 99%